Foundations in microbiology - Talaro, Kathleen; Talaro, Arthur (Dubuque, Iowa : Wm.C. Brown Publishers, 1996)
Science General
Keywords: Microbiology; Microorganisms; Microbial nutrition; Ecology; Metabolism; Genetic engineering; Chemotheraphy; Human interactions; Medical bacteriology; Environmental microbiology